Analysis of the Success of Implementing Contextual Teaching and Learning for Elementary School Students - Harahap, M. Abrar Putra Kaya; Fadillah Siregar, Amanda; Ramadhani, Fitri; Putri Arisqa, Windi; yakira Ridwan, Fitri S; Yusnaldi, Eka (Lembaga Penelitian dan Pendidikan Mandala, 2024)
An interesting and effective learning process is what every student wants, but in reality, teachers still use the lecture method in learning. Teachers still emphasize delivering material using memorized concepts. So, there is a need for alternative learning with a Contextual Teaching and Learning (CTL) model approach. The aim of this research is to find out whether learning using the CTL model is effective and interesting to apply in schools. Researchers use a literature review study method by reviewing previous literature which will be processed into valid data using qualitative data analysis. The research results show that learning with the Contextual Teaching and Learning (CTL) approach is considered important in increasing students' enthusiasm for learning in class. Learning like this will reduce students' feelings of boredom and increase their enthusiasm for learning, even though there are still obstacles that teachers will face. However, it is the teacher's job to ensure that this CTL model can run well and effectively.